Investigation into methods of recovering campylobacter spp. from river water samples - Ngoni, Nandipha (Rhodes University, Faculty of Science, Institute for Water Research)
Campylobacter species are slender, gram-negative, rod-shaped, spiral- or curved-shaped with single or pairs of flagella. They are the leading cause of diarrheal disease globally, consumption of and contact with water contaminated by faeces is a major risk factor for transmission of these organisms to humans. Rivers used for recreation and domestic and agricultural activities represent all the risk factors for Campylobacter spp. pollution and human exposure. Campylobacter spp. However, effective methods to recover Campylobacter spp. from river water samples are lacking, indicating the need for the development of more efficient methods of detection and isolation of these organisms from environmental water samples. Campylobacter detection in a water sample is critical to ascertain potential risks to humans. The aim of this study was to determine a suitable method for the detection of Campylobacter spp. from river water samples and the objectives were to (i) to evaluate the performance of different methods used for the recovery of Campylobacter spp. from environmental water samples based on Campylobacter colony count and PCR identification results, (ii) isolate and enumerate Campylobacter cells from river water samples, and (iii) identify Campylobacter spp. in river water samples. The Bloukrans River was chosen for this study because it is suspected to be contaminated by faecal inputs from nearby informal settlements without adequate sanitation, as well as untreated/insufficiently treated effluents from nearby wastewater treatment plants. First, the physicochemical quality of the river water and the presence of faecal contamination were assessed to confirm suitability for Campylobacter spp. survival and presence. Then different approaches to sample, concentrate and recover Campylobacter spp. from river water samples were assessed. The different methods assessed were (i) direct enrichment of water samples without prior concentration, (ii) prior concentration of water samples by centrifugation followed by membrane filtration of supernatant, and after that, pooling the residue and pellet together for enrichment, (iii) sampling by the Moore Swab technique. For all three methods, enrichment in Bolton broth supplemented with Bolton antibiotics was conducted. This was followed by plating on modified cefoperazone charcoal deoxycholate agar (mCCDA) and incubation under a microaerophilic atmosphere at 42Â°C for 48 h. Colony morphology, Gram staining and polymerase chain reaction (PCR) were used to identify and characterize the microorganisms. The growth of blue colonies on the mFc agar surface confirmed presence and faecal pollution of the Bloukrans River. The physicochemical properties, based on the range of pH measured at different sites of the river (between acidic 3.45 to 6.42 and alkaline 7.2 to 8.74) indicate that Campylobacter spp. can thrive in the river. Based on the results from enumeration and sequencing of colonies recovered by each method, it was discovered that the most suitable method to recover Campylobacter spp. from river water samples is by prior centrifugation (14,000 Ã— g for 30 minutes) followed by membrane filtration of the supernatant, and subsequent pooling of the residue and pellet. The pooled residue and pellet might have increased Campylobacter spp. concentrations aiding more growth during the enrichment of Campylobacter spp. from the river water samples. Results from enumerating Campylobacter spp. cells from river water samples indicate that Campylobacter spp. are present in Bloukrans River. The sequence obtained from the PCR product indicates that the species found were Campylobacter jejuni (96% homology as evaluated by BLAST). This study provided a procedure effective for obtaining a satisfactory quantitative recovery of Campylobacter spp. from environmental waters, a critical need for quantitative microbial risk assessment studies.
Keywords: Campylobacter jejuni; Stream chemistry; Organic water pollutants -- South Africa -- Eastern Cape; Water quality Measurement; Turbidity; Physicochemical process